Edukasi Stunting dan Cara Pencegahannya pada Balita di Desa Kincang Kabupaten Banjarnegara - Reni Sumanti (LPPM Universitas Harapan Bangsa Purwokerto, 2022)
One in four children under five in Indonesia is stunted. This figure is still very high when compared to the threshold set by WHO, which is 20%. The bad impact of stunting that haunts old age makes it a serious threat that requires proper handling. Lack of knowledge of mothers, wrong parenting, poor sanitation and hygiene and low health services are considered as causes of stunting. Public knowledge about stunting and its prevention needs to be improved. This method of community service is carried out using an educative or participatory approach. The activity begins with conducting an introspective survey. Discussion and evaluation were carried out after the counseling. After the socialization and education was carried out a post test was carried out with the results that 90% of mothers had good knowledge about the meaning and methods of stunting prevention. The nutritional status of children under five is strongly influenced by the understanding of parents (a mother) in managing health and nutrition in their families. Therefore, education is needed in order to change behavior that can lead to improving the nutritional health of mothers and their children.